Understanding Knowledge Sharing Barriers in Indian Health Care Sector: A Qualitative Inquiry - Murale Venugopalan, Ajay Ghosh K S, Avinash S (International Journal of Advanced Science and Technology, 2020)
In todays information  world  the  medical field  is undergoing though a  series of burgeoning  changes.  This  has  led  to  a situation   where   diagnosis  and  treatment  interventions are  affected  by  information  shared between  various members of a medical  team  comprising  of physicians and other  health care professionals.This paper  investigates how  information exchange  occurs between various health care professionals and on  barriers in sharing  knowledge  . This paper  discusses on two type of knowledge : implicit and explicit  in nature.   The researchers have adopted a qualitative approach to  identify  knowledge  enablers and barriers in health care setting. The study helped  in identifying  that communication and trust were essential in facilitating teamwork across diverse organizations (or entities).Further it add that . Miscommunication may lead to misunderstandings affecting task management, workflow, and, eventually, care of patients. Two ways of solving the communication barrier are by turning implicit knowledge into explicit knowledge and by organizing seminars to various parties on the topic.